From persuasive messages to tactics: Exploring children's knowledge and judgement of new advertising formats. (July 2018) - De Pauw, Pieter; De Wolf, Ralf; Hudders, Liselot; Cauberghe, Veroline
Despite that contemporary advertising is decreasingly about persuading children through persuasive messages and increasingly about influencing them through implicit tactics, little attention has been given to how children may cope with advertising by understanding and evaluating the new advertising tactics. Drawing on 12 focus groups entailing 60 children of ages 9–11 years, this article investigates children's advertising literacy by exploring their knowledge and judgements (and accordingly reasoning strategies) of the new advertising formats. In particular, insight is provided into children's critical reflection on the tactics of brand integration, interactivity and personalization in the advertising formats brand placement, advergames and retargeted pre-roll video ads on social media. It is shown that while children not spontaneously do so, they appear to have the ability to understand these tactics and form judgements about their (moral) appropriateness, thereby considering a wide range of societal actors.